Influence of kegel exercise on duration of healing perineal to women postpartum - Khusniyati, Etik; Purwanti, Heni (Poltekkes Kemenkes Yogyakarta, 2018)
Perineum could stitch could cause discomfort and pain impact turned into pathological rapidly. A perineal injury is easily infected and therefore requires higher care and also many factors that affect healing. The research objective was to determine the effect of Kegel exercises on the duration of second degree perineal wound healing in postpartum mothers in Dinoyo Village - Jatirejo - Mojokerto. The study design used is pre-experimental design using a design Posttest-Only Design. Dependent Variables that Kegel exercises and independent variables that long recuperation perineal wounds. The population of all postpartum mothers with perineal wound degree II in Dinoyo village obtained a sample of 13 postpartum mothers taken using the consecutive technique sampling. Then do the process of editing, coding, scoring, tabulating and served with a frequency table. The results showed that nearly all respondents a long recuperation perineal wound degree II relatively fast that is 12 respondents (92,3%). The more routine Kegel exercises can be done to accelerate the process of wound recuperation of the perineal.